Cardiovascular prevention in type 2 diabetes - Standl, Eberhardt (Henry Stewart Talks, 2013)
Diabetes mellitus as an equivalent of cardiovascular disease and secular trends of cardiovascular outcomes, Multi-factorial therapy as the golden treatment paradigm for cardiovascular prevention, Statins in primary and secondary intervention, Blood pressure lowering therapy under inclusion inhibition of the rennin-angiotensin-aldosterone system, Outcome evidence of blood glucose lowering therapy